Residence halls in perspective - Mercado, Aurea A. (Education quarterly.)
The staff of residence halls in colleges and universities vary greatly in training, interest, experience and function. Even with the most ideal conditions of residence hall life and competent personnel, it cannot be denied that there are special problems in student housing. This presentation of the character of student population, organizational program, job description of residence halls personnel and problems from the personnel point of view is intended to stimulate constructive discussions and experimentation to the end that many of the issues raised can be solved. Experience and experiment have proven that the student living center assumes an important role in providing the right climate for higher education and genuine maturity.